Juvenal's scripta matrona: Elegiac Resonances in Satire 6. - Watson, Patricia (Mnemosyne, 2007)
Scholarly work on Juvenal has focused on the poet's self-fashioning as an 'angry man'. This paper, on Satire 6, shifts the emphasis to the object of the invective, in this case the Roman matrona. In creating a character who allegedly represents the typical Roman married woman of his day, the poet constructs an anti-matrona who resembles to a large extent her polar opposite in Roman thinking—the meretrix. A major way in which this effect is achieved is via intertextual connections with Latin love elegy, and the paper offers a detailed discussion of several passages in which the wife is constructed as elegiac puella and her husband as elegiac lover.